Copper exposure reduces production of red carotenoids in a marine copepod. (November 2016) - Weaver, Ryan J.; Hill, Geoffrey E.; Kuan, Pou-Long; Tseng, Yung-Che
Highlights: ⿢ Production of the red carotenoid, astaxanthin, was reduced during copper exposure. ⿢ Copper exposure also induced upregulation of mitochondrial and antioxidant genes. ⿢ Astaxanthin production may signal sub-lethal effects of marine pollution in copepods. Abstract: Sub-lethal exposure to copper has been shown to modulate both mitochondrial function and antioxidant gene expression in zooplankton. To date, however, researchers have not identified a quantifiable phenotypic trait that reliably indicates such physiological responses to copper exposure. Red ketocarotenoids are abundant in marine zooplankton serving both physiological and coloration roles, and their production is sensitive to environmental stress. In this study the expression of mitochondrial gene cytochrome c oxidase I (COI) and antioxidant gene glutathione reductase (GR), and the production of red ketocarotenoid, astaxanthin, was measured in response to sub-lethal copper exposure. We found that mRNA of COI and GR was more abundant in copper-exposed copepods than controls, suggesting there was a physiological response to copper exposure. At the same time, copper-exposed copepods produced less astaxanthin than controls. We suggest that ketocarotenoid content of zooplankton has the potential to be a sensitive bioindicator of marine environmental pollution. Understanding how cellular responses to environmental stressors manifest in the phenotypes of marine animals will greatly increase our capacity to monitor marine ecosystem health.